2005
DOI: 10.1002/polb.20513
|View full text |Cite
|
Sign up to set email alerts
|

Influence of entanglements on glass transition of atactic polystyrene

Abstract: Freeze‐dried samples were prepared from dilute solutions of atactic polystyrene (a‐Ps) in benzene in a concentration range of 1 × 10−1 to 2 × 10−5 g/mL, and their glass transition temperatures (Tg) were determined by differential scanning calorimetry. It was found that below a critical concentration (C), the Tg of samples decreases linearly with decreasing logarithmic concentration of solutions. The freeze‐dried samples were annealed at a constant temperature for various times or at various temperatures for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 44 publications
6
39
0
Order By: Relevance
“…[10,11] It is found that no depression in T g occurs for polymer concentrations greater than a critical value (ca. 1!10 K3 g/ml for polystyrene) and that depressions increase as the polymer concentration decreases [6,[9][10][11]; for example, in the early work of Braun and Kovacs, no T g depression is reported for polystyrene freeze-dried from a 1% solution in benzene [15]. Although a depression in T g upon freeze-drying from dilute solution is the general result, an increase in T g upon freezedrying from dilute solution is observed [12,13] for polyacrylamide, which has strong hydrogen bonding.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…[10,11] It is found that no depression in T g occurs for polymer concentrations greater than a critical value (ca. 1!10 K3 g/ml for polystyrene) and that depressions increase as the polymer concentration decreases [6,[9][10][11]; for example, in the early work of Braun and Kovacs, no T g depression is reported for polystyrene freeze-dried from a 1% solution in benzene [15]. Although a depression in T g upon freeze-drying from dilute solution is the general result, an increase in T g upon freezedrying from dilute solution is observed [12,13] for polyacrylamide, which has strong hydrogen bonding.…”
Section: Introductionmentioning
confidence: 96%
“…The magnitude of the change in T g upon freeze-drying from dilute solution depends on the details of sample preparation and the sample itself [2][3][4][5][6][7][8][9]. For example, very large T g depressions, 40-64 K, are reported for polystyrene freeze-dried from dilute cyclohexane solutions [2,3], whereas depressions of between 2 and 15 K have been reported for various polystyrenes freezedried from dilute benzene solutions.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations